The largest known bear, Arctotherium angustidens, from the early Pleistocene Pampean region of Argentina: with a discussion of size and diet trends in bears - Soibelzon, Leopoldo Héctor (2011)
The South American giant short-faced bear (Arctotherium angustidens Gervais and Ameghino, 1880) is one of five described Arctotherium species endemic to South America and it is known for being the earliest, largest, and most carnivorous member of the genus. Here we report an extraordinarily large A. angustidens individual exhumed from Ensenadan sediments (early to middle Pleistocene) at Buenos Aires Province, Argentina. Based on overall size, degree of epiphyseal fusion, and pathologies, this bear was an old-aged male that sustained serious injuries during life. Body mass of the bear is estimated and compared to other ursid species based on a series of allometric equations. To our knowledge, this specimen now represents the largest bear ever recorded. In light of this discovery, we discuss the evolution of body size in Arctotherium (from large-to-small) and compare this to bears that exhibited different evolutionary trajectories. We suggest that the larger size and more carnivorous nature of A. angustidens, compared to later members of the genus, may reflect the relative lack of other large carnivores and abundance of herbivores in South America just after the Great American Biotic Interchange.